Utility of internal markers to improve the accuracy of cystic fibrosis genotype analysis - Raskin, S (BioTechniques, 1992)
DNA diagnostic tests often utilize restriction endonuclease digestion of PCR-amplified portions of genes under analysis. When partial digestion occurs, the resulting patterns may lead to error in diagnosis. To overcome such potential errors in cystic fibrosis testing, we have developed internal markers that can increase the precision and reliability of genotype assignments